Facet joint remodeling in degenerative spondylolisthesis: an investigation of joint orientation and tropism - Berlemann, U. (Springer-Verlag, 1998)
This study analyzed transverse facet joint angulations at the three lower lumbar levels in 132 patients assigned to one of four groups. Group A comprised 23 patients with degenerative spondylolisthesis (DS) at the level L4-5, group B comprised 40 patients above the age of 50 years, group C comprised 38 patients aged between 35 and 50 years, and group D comprised 31 patients under the age of 35 years. Groups B, C, and D had no evidence of DS. Measurements were taken from hard copies of axial MR or CT images. The transverse plane of facet joints was more sagittally oriented in group A than in any other group. This difference was highly significant at the L4-5 level. The incidence of more sagittally oriented L4-5 facet joints was also significantly higher only in group A. The incidence of facet joint tropism, however, was not different in group A. These results support the view that the pronounced sagittal alignment of facet joints in patients with DS represents a secondary remodeling rather than a pre-existing morphology. Facet joint asymmetry does not seem to play a major role in the development of DS.